Determinants of renewable energy implementation: A case-study of Ostrobothnia region Finland - Akhtar, Muhammad Faisal (My University, 2014)
Ever rising carbon levels and environmental footprints resulting from energy generation activities are devastating impacts being registered on planet earth. Environmental concerns coupled with threats of globally fluctuating oil prices posing huge economic burdens are bringing a progressive change in society. These factors are provoking the heightened sense of energy security and effective deployment of natural resources. It is eventually leading universe towards a carbon free energy sustainable technologies in the form of renewable energies. Despite of influential effect of existing energy market players, renewables have started to emerge as sustainable energy future. This study represents the important determinants that are motivating for the implementation of renewable energy in one of the municipality in Finland. This country clearly represents an example of technologically advanced countries with long rooted expertise and highly committed behavior in the development and implementation of energy technology on global level. Various different literature studies provide a deep comparative insight to different factor for the implementation of renewable energy as a literary framework followed a sequential examination of these factors under the criticism conducted by data collected. After performing a comparative analysis, a final model of motivating determinants has been presented. This study presents an insight to the motivating determinants for the implementation of renewable energy technologies in Finland and provides future suggestions for further studies.
Keywords: Renewable Energy; Ostrobothnia; Determinants; Environment; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|; fi=Digitaalinen media|en=Digital media|